An Acute Gastroenteritis Outbreak Linked to Serving Hot Meals Inside Polybag During a Religious Ceremony, Bangladesh‐2022: A Retrospective Cohort Study - Immamul Muntasir; Mohammad Rashedul Hassan; Md. Omar Qayum; Quazi Ahmed Zaki; Mahbubur Rahman; Tahmina Shirin (Health Science Reports, 2026)
ABSTRACT Background and Aims Foodborne outbreaks frequently manifest as acute gastroenteritis (AGE) and are threat for public health in Bangladesh. On 17 November 2022, the health‐manager of Delduar sub‐district, Tangail reported an AGE outbreak to the Institute of Epidemiology, Disease Control and Research (IEDCR). A team was deployed to investigate the source and risk factors of the outbreak and contain it. Methods We conducted a retrospective cohort study after verifying that all cases ate food of a religious ceremony (Mahfil) on 13 November, 2022. We defined a case as any person from Gojiabari who developed acute watery diarrhea with or without fever, vomiting, or abdominal cramp after eating food from the Mahfil. We interviewed every person who ate the Mahfil‐food with structured questionnaires. Stool and water samples were analyzed for enteric pathogens. Food‐specific attack rates (AR) and relative risks (RR) were calculated to identify risk factors. Results Overall AR was 57% (229/400). Median incubation period was 13 h [Inter‐Quartile‐Range (IQR): 10–19 h]. Most common symptoms were diarrhea (100%), fever (75%) and vomiting (34%). The epidemic curve suggested a point‐source outbreak. 224 of 329 persons who ate khichuri (rice and lentils) served in a polybag (AR = 68%, RR = 9.7, 95% CI = 4.1–22.6) developed illness compared to 5 of 70 who ate on plate (AR = 7%, RR = 0.1, 95% CI = 0.05–0.25). Khichuri was placed on Banana‐leaves immediately after cooking in a kitchen with inadequate sanitation and packaged in polybags without proper cooling. Stool and water samples were negative for Vibrio cholerae, Salmonella and Shigella . Conclusions The outbreak was strongly associated with packaging hot khichuri in polybags. To prevent a similar outbreak, we recommend maintenance of hygiene during food processing and proper cooling of food before packaging.